Do corporate governance and top management team diversity have a financial impact among financial sector? A further analysis - Ebrahim Mohammed Al-Matari (Cogent Business & Management, 2022)
The paper examines the connection between the top management team determinants and corporate governance in Saudi Arabia's financial listed companies. The study covers the financial sector for five years from 2014 to 2018. Moreover, feasible general least squares regression is used to run the association between independence variables and dependence variable. In addition, it is used for further analysis to make sure if the main finding results are similar or different. The results of the panel data from the FGLS regression indicated the predictors' effects on the corporate performance. The outcome from the statistical analysis of the model indicated that board size, audit committee independence and audit committee meeting have significantly effect of financial performance. Besides, size, accounting and finance experience and general experience of top management team have significantly association to the financial performance of the Saudi listed firms. Further analyses found that board size, general experience of top management have a negative association with corporate performance. On contrary, the board independence, board commitment, size of TMT, accounting and finance experience of TMT and education level of TMT have a positive significantly relationship with corporate performance. The study provides detailed information for academic in terms of the relationship of good strategy used by top management teams and corporate governance, which should be considered to provide the best practices of such teams. Finally, the outcomes of the study unlock up road for future examinations among developing countries.
Keywords: C22; G30; G34; 650; Corporate governance; Financial performance and Saudi Arabia Stock; Top management team diversity